Deep Learning Practices in the Merdeka Curriculum in Elementary Schools: A Field Study at SDIT Najaahan - Susanti; Ayu Puji Rahayu; Hesti; Desya Candra Dewi (International Journal on Education Issues, 2026)
Purpose – This study aims to investigate the practice of immersive learning in the implementation of Merdeka Curriculum in elementary schools, highlighting the learning process, assessment, and documentation as key aspects that still leave gaps in curriculum implementation. This study seeks to provide a deeper understanding of the dynamics of implementing immersive learning as a pedagogical practice in the context of elementary education. Design/Methodology/Approach – This study employed a descriptive qualitative approach with a field study design. Data were collected through triangulation of methods, including observation of the learning process, semi-structured interviews, and analysis of learning documents, including teaching modules, assessment instruments, and student project results. Data were analyzed using an analytical model encompassing data reduction, data presentation, and the drawing and verification of conclusions. Findings – The results indicate that the practice of immersive learning in the Merdeka Curriculum has been implemented effectively across aspects of the learning process and student learning outcomes, characterized by active student engagement, the use of tasks oriented towards higher-order thinking skills, collaboration, and the role of teachers as learning facilitators. However, this study also identified challenges with the consistency of portfolio documentation and the governance of learning projects, particularly in the upper grades, with implications for the ongoing monitoring of student learning progress. Originality/Value – This study offers an empirical perspective on deep learning as a pedagogical practice in the implementation of the Merdeka Curriculum in elementary schools. The findings broaden understanding of the importance of integrating learning processes, authentic assessments, and portfolio documentation in supporting meaningful and sustainable learning, and provide practical implications for schools and teachers in strengthening the implementation of the Merdeka Curriculum.